Pengembangan Media Pembelajaran berbasis Aplikasi Ispring pada Materi Desain Grafis di Kelas X SMK Negeri 5 Malang - Bagus Setiawan; Satrio Hadi Wijoyo; Wibisono Sukmo Wardhono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
In the world of education there is a learning and teaching process between teachers and students. In the learning and teaching process, the teacher's way of delivering good material is closely related. Along with the development of the times, a teacher is required to provide effective and efficient learning materials, but many teachers do not understand how to provide good learning media, even though learning media has a lot of influence in the learning process. Theapplication Ispring is one of the means for teachers to be able to develop effective and efficient learning media, where the application can create a learning media that can be accessed via an Android smartphone, so it is hoped that student interest in learning can increase. The purpose of this study was to determine the procedure for developing instructional media and to measure the effectiveness of the use of learning media based on the application Ispring to improve student learning outcomes. This study uses the ADDIE development model which consists of five stages, namely analysis, design, development, implementation and evaluation. The results showed that the use of learning media based on the Ispring application was feasible to be used in the learning process and was able to improve student learning outcomes in Graphic Design subjects in class X SMK Negeri 5 Malang. This is evidenced by the passing results of five students who have worked on the quizzes that have been given to the application-based learning media Ispring on graphic design material in class X SMK Negeri 5 Malang.